2019
DOI: 10.1111/csp2.130
|View full text |Cite
|
Sign up to set email alerts
|

Fire disturbance influences endangered Cape Sable Seaside Sparrow (Ammospiza maritima mirabilis) relative bird count

Abstract: Periodicity of fire disturbance is a known driver of ecosystem function and is reported as important in both promoting and maintaining viable breeding habitat for the endangered Cape Sable Seaside Sparrow (Ammospiza maritima mirabilis; CSSS). In south Florida, the CSSS serves as a fine‐scale indicator of the marl and mixed‐marl prairie communities of the Florida Everglades. The CSSS distribution is affected by numerous well‐documented physical drivers, including water depth and fire regime. Here, we fit zero‐i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
(34 reference statements)
1
10
0
Order By: Relevance
“…Variation in (A) soil total phosphorus (TP) concentrations, (B) total nitrogen to total phosphorus (TN:TP), and (C) total carbon to total phosphorus mass ratios (TC:TP) with increasing time since last fire (TSLF) in the marl soils (MS) inside Everglades National Park. highest at a fire return interval of 5-8 yr (Benscoter et al 2019). We believe that fire is also beneficial for the other soil and hydrologic types analyzed (i.e., richer soils with intermediate or long hydroperiod), which, in our opinion, should not be left unburned for long periods of time either.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Variation in (A) soil total phosphorus (TP) concentrations, (B) total nitrogen to total phosphorus (TN:TP), and (C) total carbon to total phosphorus mass ratios (TC:TP) with increasing time since last fire (TSLF) in the marl soils (MS) inside Everglades National Park. highest at a fire return interval of 5-8 yr (Benscoter et al 2019). We believe that fire is also beneficial for the other soil and hydrologic types analyzed (i.e., richer soils with intermediate or long hydroperiod), which, in our opinion, should not be left unburned for long periods of time either.…”
Section: Discussionmentioning
confidence: 74%
“…While the maximum fire return interval recommended here is solely based on our observation of soil TP that may vary when other aspects of ecosystem characteristics are considered. For instance, the short‐hydroperiod MS is primary habitat of Cape Sable seaside sparrow (CSSS; Ammodramus maritimus mirabilis ), and its habitat is adversely affected if the area is left unburned for longer period (Pimm et al 2002), as CSSS population has been found highest at a fire return interval of 5–8 yr (Benscoter et al 2019). We believe that fire is also beneficial for the other soil and hydrologic types analyzed (i.e., richer soils with intermediate or long hydroperiod), which, in our opinion, should not be left unburned for long periods of time either.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate a quadratic relationship between time since fire and both CSSS bird count and site occupancy patterns, with the greatest bird count between 5 and 8 yr since fire (data from 1992−2014; Benscoter et al 2019) and the highest occupancy from 6 to 11 yr since fire (data from 1989−2005; La Puma 2010). A detailed study after the Lopez fire, a large human-ignited fire in the southern area of subpopulation E, showed that densities of the CSSS and nest success declined for 2 yr after the fire, but then returned to levels comparable to adjacent un burned areas 3 yr after the fire (La Puma et al 2007).…”
Section: Fire and Habitatmentioning
confidence: 99%
“…A recent assessment points again to potentially positive effects of fire (Benscoter et al, 2019). Annual counts conducted from 1992 to 2014 found higher sparrow numbers 5-8−years after a burn; numbers also improved in relation to the proportion of the area burned within 16 ha of each census station (Benscoter et al, 2019).…”
Section: Communication and Application Of Fire Researchmentioning
confidence: 99%
“…A recent assessment points again to potentially positive effects of fire (Benscoter et al, 2019). Annual counts conducted from 1992 to 2014 found higher sparrow numbers 5-8−years after a burn; numbers also improved in relation to the proportion of the area burned within 16 ha of each census station (Benscoter et al, 2019). Error bars about the estimates were broad and point to the need for additional research, but marl prairies in ENP will burn at some point, perhaps under wildfire conditions that will be difficult control.…”
Section: Communication and Application Of Fire Researchmentioning
confidence: 99%